2020
DOI: 10.1111/aos.14719
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term results of rescue photodynamic therapy for type 1 neovascularization refractory to anti‐vascular endothelial growth factor

Abstract: Purpose To evaluate long‐term results of photodynamic therapy (PDT) as a rescue treatment in patients with type 1 neovascularization refractory to intravitreal anti‐vascular endothelial growth factor (VEGF). Methods Patients who underwent reduced‐fluence PDT for refractory type 1 neovascularization, which showed persistent subretinal and/or intraretinal fluid after three or more consecutive anti‐VEGF treatments, and were followed up for ≥24 months were reviewed. Results Seventy‐eight eyes of 78 patients were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Multiple studies have evaluated various PDT protocols in the treatment of anti-VEGF-resistant eAMD. Park et al retrospectively evaluated 78 eyes with anti-VEGF-resistant eAMD treated with reduced fluence PDT (laser delivered for a shorter period of time resulting in a 20% reduction in energy density delivered from standard therapy) [ 77 ]. All enrolled eyes initially received PDT as “rescue therapy” based on a lack of resolution of subretinal and/or intraretinal fluid along with macular thickening despite a series of three anti-VEGF injections.…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%
“…Multiple studies have evaluated various PDT protocols in the treatment of anti-VEGF-resistant eAMD. Park et al retrospectively evaluated 78 eyes with anti-VEGF-resistant eAMD treated with reduced fluence PDT (laser delivered for a shorter period of time resulting in a 20% reduction in energy density delivered from standard therapy) [ 77 ]. All enrolled eyes initially received PDT as “rescue therapy” based on a lack of resolution of subretinal and/or intraretinal fluid along with macular thickening despite a series of three anti-VEGF injections.…”
Section: Exudative Age-related Macular Degenerationmentioning
confidence: 99%
“…However, a recent study has demonstrated different results. In the study by Park et al, rescue PDT was beneficial in resolving fluid and improving visual acuity in refractory Type 1 neovascularization, including PCV [17]. This suggests that PDT can be considered as an alternative to aflibercept-resistant PCV.…”
Section: Discussionmentioning
confidence: 97%
“…16 The typically small and retrospective studies examining the use of combination therapies for refractory NVAMD demonstrated anatomical benefits and reduced anti-VEGF treatment burden without corresponding improvements in BCVA. [10][11][12][13]15,16 Tozer et al 14 reported both anatomical and functional improvements with combined anti-VEGF therapy and photodynamic therapy, but this study used a less stringent definition of "refractory NVAMD" including patients with as few as three prior anti-VEGF injections (mean prior injections: 4.9).…”
Section: Discussionmentioning
confidence: 99%
“…8,9 A variety of alternative treatment strategies have been investigated in the attempt to achieve complete macular drying in eyes with refractory NVAMD. These include increasing the dose of the anti-VEGF agent injected 10,11 and combining anti-VEGF therapy with intravitreal steroids, 12,13 photodynamic therapy, 14,15 and topical aqueous humor suppressants. 16 The typically small and retrospective studies examining the use of combination therapies for refractory NVAMD demonstrated anatomical benefits and reduced anti-VEGF treatment burden without corresponding improvements in BCVA.…”
Section: Discussionmentioning
confidence: 99%